2009
DOI: 10.1007/s11293-009-9181-y
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Adolescents and On-time High School Graduation: Racial and Gender Disparities

Abstract: Adolescents, Obesity, Overweight, BMI, On-time high school graduation, Propensity scores, Add Health, I00,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
0
8
1
Order By: Relevance
“…Obese adolescents in both of these groups are about 12 percent less likely to complete a college degree than non-obese adolescents. 8 Other research has found, for females but not males, a negative relationship between adolescent obesity and high school performance (Sabia, 2007) and on-time graduation (Okunade et al, 2009). In contrast, our results suggest that the negative effects of obesity on academic attainment for females occur primarily at the level of the college degree.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Obese adolescents in both of these groups are about 12 percent less likely to complete a college degree than non-obese adolescents. 8 Other research has found, for females but not males, a negative relationship between adolescent obesity and high school performance (Sabia, 2007) and on-time graduation (Okunade et al, 2009). In contrast, our results suggest that the negative effects of obesity on academic attainment for females occur primarily at the level of the college degree.…”
Section: Resultscontrasting
confidence: 60%
“…This might be the case if early obesity affects human capital acquisition and productivity. Indeed, research has found negative effects of obesity on youth academic performance (Datar, 2004;Mo-suwan et al 2009), high school graduation rates (Sabia, 2007;Okunade et al 2009), and the probability of attending college (Crosnoe, 2007). Since education is strongly and positively associated with lifetime earnings and other quality of life indicators, child or adolescent obesity may therefore affect adult earnings and other outcomes indirectly, even if no direct relationship exists.…”
Section: Introductionmentioning
confidence: 99%
“…Given the current steep rise in the prevalence of childhood obesity in these countries [ 1 ], if there is an association between obesity and academic achievement in these contexts, the subsequent economic impact of obesity-related deficits may have even more implications for economic growth of middle-low-income countries and for human capital. Prospective cohort studies indicated that adolescent obesity is negatively associated with years of schooling [ 76 , 77 ], school completion [ 78 ], enrolment in higher education [ 79 , 80 ], income [ 76 , 77 , 81 ] and employment status [ 82 ]. The economic argument for the implementation of effective childhood obesity prevention and treatment programmes could therefore be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an estimated bias would occur by leaving out the income variable from our analysis. Similarly, we know that obesity is related to lower levels of educational attainment, and anemia is related to lower enrollment rates in schooling (17,18,19). Taken together, leaving out a control variable for education would bias our estimate of the relationship between BMI and iron deficiency, as it would be picking up these variable's additional relationships with educational attainment.…”
Section: Methods and Proceduresmentioning
confidence: 96%